Efficient Access to Chiral β‐Borylated Carboxylic Esters via Rh‐Catalyzed Hydrogenation. Issue 12 (11th April 2019) - Liu, Gang; Li, Anqi; Qin, Xueyuan; Han, Zhengyu; Dong, Xiu‐Qin; Zhang, Xumu
Abstract: Rh/bisphosphine−thiourea ligand (ZhaoPhos)‐catalyzed asymmetric hydrogenation of ( Z )‐β‐substituted‐β‐boryl‐α, β‐unsaturated esters was successfully developed, furnishing a variety of chiral β‐borylated carboxylic esters with high yields and excellent enantioselectivities (up to 99% yield and >99% ee). The gram‐scale asymmetric hydrogenation was performed efficiently in the presence of only 0.05 mol% (S/C=2 000) catalyst loading with full conversion, 99% yield and 99% ee. Moreover, the hydrogenation product was easily converted to other versatile synthetic intermediates, such as methyl ( S )‐3‐hydroxy‐3‐phenylpropanoate and methyl ( S )‐3‐(furan‐2‐yl)‐3‐phenylpropanoate. Abstract :